Analysing the emergency department patient journey: Discovery of bottlenecks to emergency department patient flow. (8th November 2016) - Khanna, Sankalp; Boyle, Justin; Good, Norm; Bell, Anthony; Lind, James
Abstract: Objective: Despite significant workflow reform to comply with the federally mandated National Emergency Access Target (NEAT), Australian public hospitals continue to face significant barriers in achieving good ED patient flow. This study was undertaken to identify and analyse the impact of individual waypoints on an ED patient's journey and identify which waypoints act as bottlenecks to a hospital's 4 h ED disposition performance. Methods: This study involves retrospective analysis and simulation employing 2 years of ED administrative data from a sample of two major and two large metropolitan hospitals in Queensland, Australia. The main outcome measures included waypoint wait times (Treatment Delay and Departure Delay), ED length of stay (EDLOS) and compliance with the NEAT target, measured for all (overall NEAT) and admitted (Admitted NEAT) patients. Variations in outcome measures were analysed as functions of hour of day, day of week, departure status and triage category. Simulations identified the impact of potential ED workflow changes in the context of NEAT performance. Results: Departure Delay accounted for 60 and 20% of EDLOS across large and major metropolitan hospitals, respectively. Higher gains in NEAT compliance are associated with improvements in departure delay rather than treatment delay. Simulation identified that halving Departure Delay improves Admitted NEAT by up to 22 and 4% at large and major metropolitan hospitals, respectively. Conclusions: The results reinforces the need for a whole‐of‐hospital effort to address flow bottlenecks, and identify moving a patient from emergency to inpatient care as the critical bottleneck in ED system performance.